(untitled) (Південний архів (історичні науки), 2024)
The purpose of the work should be to consider the factors that led to the formation of the image of the Russian aggressor on the example of the Kherson region as a socio-cultural and political frontier of the beginning of the 21st century. This will make it possible to understand not only the form and limits of the perception of the Russian occupation, but also changes in the perception of the anti-civilizational form of development that Russia is currently presenting. Research results. The Russian temporary occupation of the Kherson region in 2022 determined the main features of the reflection of the local population due to the influence of the socio-cultural and political frontier of the region. The main factors in the formation of the general image of Russians in the role of the enemy should be named: external informational influence, forms of personal communication with the military of the aggressor country, the level of national self-identification, the presence of loved ones and relatives in the ranks of the armed forces of Ukraine, the scale of material and personal non-material losses, the presence of psychological ties to the Soviet heritage, and first of all, the reaction to the behavioral manifestations of the Russian occupiers’ vision of the Ukrainian population. Conclusions. The analysis of the sources indicates the creation of a differentiated image of Russian soldiers and the occupation by the inhabitants of the city and the countryside. It can be noted that despite the presence of common features in the negative perception of the enemy, there are certain differences between them in the perception of real and potential dangers of the occupation, which are determined by: opportunities for survival (availability of food, adaptation to a critical minimum of living conditions, etc.), the level of distance in communication between the occupied and the occupiers, the level of direct threat depending on socio-political, civil status and the level of defining national identity. The occupation of Kherson region in the modern global war unleashed by the Russians is a good example not only of the aggressor’s use of various military and propaganda powers, but also of ways of countering this centuries-old Moscow expansion, which is based on the formation of the true image of the aggressor.